EFFECT OF SLEEP ON SERUM TESTOSTERONE LEVELS IN YOUNG MALE PATIENTS WITH DEPRESSION - Badar, Ahmed; Khoja, Akbar Ali; Sultan, Norin; Yousafzai, Aziz ur Rehman (Journal of Ayub Medical College Abbottabad, 2000)
Background: In our previous study we have reported that the testosterone levels of the young male patients with depression are significantly less than the testosterone levels of controls. In this study we report the effect of sleep on the serum testosterone levels of the same subjects. Methods: A pre-sleep sample and a post-sleep sample of blood was taken on two consecutive nights. Strict criteria for assuring the quality of sleep were observed. Testosterone was measured by radioimmunoassay, and the results were compared for statistical significance. Results: There was a highly significant rise of serum testosterone levels in the post-sleep samples of controls. The same rise was negligible in the patients with depression. Conclusion: In young male patients with depression the normal response of serum testosterone to sleep is impaired. This may be related to the etiology or severity of depression.